Umar bin Al-Khattab's Interpretation and Practice of Surah Al-Maidah 51 in the Hadith Mawquf - Adyatama, Muhammad Fajar; Roziqi, Ahmad Masrur (Ijtihad, 2023)
**English**Umar bin Khattab once argued with Surah Al Maidah verse 51 to refuse the appointment of state officials from non-Muslim circles even though he fulfilled the requirements and qualifications stated in the Mauquf hadith. Umar's position as supreme leader at that time gave him the authority to refuse the appointment of non-Muslims as state officials in countries with a majority Muslim population. Apart from that, the majority of classical and contemporary scholars are of the opinion that non-Muslims are prohibited from becoming leaders over Muslims. Based on the story that occurred during Sayyidina Umar's time, in this article the author aims to discuss text interpretation methods to explore the meaning contained in this event. The method used is descriptive qualitative. The results of this research are that in the Qur'an, leadership is fundamental, so a leader must be fair, trustworthy, careful and uphold amr al-ma'ruf wa nahy mungkar. The law of electing non-Muslim leaders in Muslim-majority countries is haram as stated in the Al-Qur'an surah al Maidah 51 which was later used as an argument by Sayyidina Umar bin al Khattab to reject the high position of a dzimmy infidel. in his government. Apart from that, some scholars believe that it is haram to elect non-Muslim leaders. There are some ulama who provide leniency/moderation by providing conditions if it is permitted in an emergency. Even so, the Indonesian Ulema Council issued a fatwa stating that electing non-Muslim leaders is haram. **Indonesia**Khalifah Umar bin Khattab pernah berhujjah dengan surat al Maidah ayat 51 untuk menolak pengangkatan pejabat negara dari kalangan non muslim meskipun ia memenuhi syarat dan kualifikasi yang tertuang dalam hadis mauquf. Posisi Umar sebagai pimpinan tertinggi kala itu menjadikan ia berwenang untuk menolak pengangkatan non muslim menjadi pejabat negara di negara yang mayoritas penduduknya muslim. Selain itu, mayoritas ulama klasik dan kontemporer berpendapat bahwa non muslim dilarang menjadi pemimpin atas umat Islam. Berdasarkan kisah yang terjadi di masa Sayyidina Umar itu, dalam artikel inipenulis bertujuan untuk mebahasas metode tafsir teks untuk menggali maksud yang terkandung dalam peristiwa tersebut. Metode yang digunakan adalah kulaitatif deskptif. Hasil dari penelitan ini bahwa dalam Al-Qur’an kepemimpinan merupakan hal yang mendasar, sehingga seorang pemimpin harus bersikap adil, amanah, berhati-hati dan menegakkan amr al-ma`ruf wa nahy mungkar. Hukum memilih pemimpin non-Muslim di negara mayoritas Muslim adalah haram sebagaimana tertuang dalam Al-Qur'an surah al Maidah 51 yang kemudian dijadikan dalil Sayyidina Umar bin al Khattab untuk menolak kedudukan tinggi seorang kafir dzimmy. dalam pemerintahannya. Selain itu, sebagian ulama berpendapat haram memilih pemimpin non-Muslim. Ada sebagian ulama yang memberikan kelonggaran/moderat dengan memberikan syarat bila dalam keadaan darurat diperbolehkan. Meski begitu, Majelis Ulama Indonesia, memberikan fatwanya bahwa memilih pemimpin non-Muslim adalah haram.